ADJEKTIF BAHASA ARAB DAN MELAYU - SATU ANALISIS KONTRASTIF - Muhammad Hafizuddin Hussin; Maimun Aqsha Lubis (STIT Al-Ittihadiyah Labuhanbatu Utara, 2019)
Previous studies have shown that mastery of Malay students of Arabic Language is at a low and unsatisfactory level.Malay Students will not be able to get away from doing mistakes, especially during translation and understanding Arabic adjectives that have many differences and similarities. For example during translation, students will be confused about whether a word is an adjective or a noun. This is the factor that makes the researcher interested in doing the contrasting analysis. This study aims to identify the characteristics of Malay and Arabic adjectives, and to analyze their similarities and differences. The systematic analysis was then performed. The findings revealed that there are many similarities and differences that need to be known by educators of both languages ​​so that they are able to understand the problems and confusion faced by the students, especially those related to adjectives Malay and Arabic such as the sentence’s structure whereas adjectives should be. For example adjective in Malay can be predicate directly such as ‘Kucing itu comel’ but in Arabic there must be another word as predicate and adjective should be added later such as ‘القطّ حيوان جميل’ .It is also proven that the word ‘yang’ which means ‘that’ undeniably plays an important role in translating Malay-Arabic adjectives and avoiding confusion in translation for exmple ‘Itu seekor kucing yang comel, ذلك قطّ جميل so that it it will not be misunderstood as ‘Kucing itu comel, ذلك القطّ جميل ’.